Evidence for the role of demyelination, HLA-DR alleles, and cytokines in the pathogenesis of parvovirus B19 meningoencephalitis and its sequelae. Issue 6 (1st December 2002) - Kerr, J R; Barah, F; Chiswick, M L; McDonnell, G V; Smith, J; Chapman, M D; Bingham, J B; Kelleher, P; Sheppard, M N
Abstract : Objective: To review the clinical and pathological features of parvovirus B19 meningoencephalitis and its sequelae in 12 previously published cases, and to perform additional tests to determine the pathogenesis of the disease. Methods: Cases were reviewed and available serum and cerebrospinal fluid (CSF) tested for antiganglioside antibodies and a range of cytokines. In situ hybridisation for parvovirus B19 DNA was performed on postmortem brain tissue in two cases. HLA-DRB1 typing was undertaken on genomic DNA extracted from peripheral blood leucocytes. Results: Cerebellar involvement was suggested either clinically or pathologically in four cases. In the two cases with postmortem histology, there was marked atrophy of the molecular and granular layers of the cerebellum with focal loss of Purkinje cells. Brain scanning by MRI or CT was done in six cases during the acute phase. Three were abnormal with evidence of demyelination. Three had markedly enlarged ventricles, in two of which there was high signal intensity from the white matter on both T1 and T2 weighted images. The three cases with abnormal brain scans had long term neurological sequelae (mental retardation, personality change, altered affect). In situ hybridisation on available postmortem brain tissue was negative in the two cases tested. All cases in which HLA-DR alleles were determined carried at least one of the following alleles: HLA-DRB1*01, *04, *07, *09, *15, *16. Available serum and CSF was tested for antiganglioside antibodies (all negative) and for a panel of cytokines, which had a similar profile in both serum (n = 5) and CSF (n = 1) during the acute phase. Cytokines that were consistently detectable were IL-6 (mean 726.20 pg/ml), TNFα (50.64 pg/ml), IFNγ (39.64 pg/ml), GM-CSF (216.12 pg/ml), and MCP-1 (154.43 pg/ml); IL-1β, IL-5, and IL-13 were undetectable. Conclusions: HLA-DR associations, an increased cytokine response, and benefit from immunomodulatory treatment (in one case) support a role for the immune response in the pathogenesis of parvovirus B19 meningoencephalitis.